Tensile strength of single continuous fiber extracted from mengkuang leaves - Hamizol, M.S. (Penerbit UTM Press, 2015)
The focus of this paper is to obtain a continuous cellulose fiber (CCF) from mengkuang leaves of the pandanus genus using chemical extraction process and to measure its tensile properties. The higher the concentration of sodium hydroxide (NaOH) and the longer soaking times employed during the alkaline treatment of the mengkuang leaves, the higher the cellulose content extracted. The highest tensile strength of 520 MPa was measured for single CCF treated with optimum extraction parameters of 2 NaOH for 60 minutes. Amount of cellulose content of the extracted fiber showed an inverse relationship with the fiberâs tensile strength. The removal of lignin and hemicellulose content during extraction process may have caused the reduction in the fiberâs tensile strength. Â© 2015, Penerbit UTM Press. All rights reserved.